TEMP Victorian Alpine Plot Network (Alpine Summit Plots): Vegetation Composition Data, South-East Highlands, Australia, 2015. - John Morgan (TERN Australia, 2014)
This Victorian Alpine Plot Network Vegetation Composition Data Package comprises plot-based vegetation data for alpine mountain summits in the Australian Alps. Twenty 1 metre squared quadrats are situated along each of four varying length permanent transects established on mountain summits. In each quadrat, plant species are assigned percentage cover abundance and species per metre squared are recorded. The Alpine Summit plots study, which commenced in 2001, forms part of the collection of data packages by the Victorian Alpine Plot Network. A synopsis of related data packages which have been collected as part of the Victorian Alpine Plot Network’s full program is provided at http://www.ltern.org.au/index.php/ltern-plot-networks/victorian-alpine.